Corruption Perception And Tax Non-Compliance Among Self-Employed Individuals In Ghana - Odartey, E.L. (University Of Ghana, 2022)
This thesis assesses perceived corruption and tax non-compliance in Ghana within the informal sector; and investigates some key factors that lead to tax non-compliance among individuals within the informal sector of Ghana. Based on a review of the theory of planned behaviour, the study evaluated the impact of perceived corruption, trust in government, tax rate fairness, tax system complexity and religiosity on tax non-compliance. In addition, the study investigates the moderating role of religiosity on the relationships between perceived corruption, trust in government, tax rate fairness, tax system complexity and tax non-compliance. A total of 598 valid responses were received from individuals working within the informal sector. The data was collected via a self-administered questionnaire. A structural model analysis employing the Partial Least Square based on the Structural Equation Modelling technique was used to test the study's hypothesized relationships. The result of the study indicates that individuals with a higher level of perceived corruption are more likely to engage in tax non-compliance. The study further reveals that tax system complexity leads to high levels of tax non-compliance within the informal sector. When individuals are frustrated by the tax system as a whole, they end up evading taxes. The result indicates that tax rate fairness, trust in government and religiosity are negatively related, which suggest individuals in the informal sector would be motivated to comply when they perceive the government and tax system to be transparent. Furthermore, religiosity was able to moderate the relationships between the factors that influence tax non-compliance behaviour. The findings from the study are beneficial to the tax authorities, managers of firms and policy makers in establishing ways to mitigate the occurrence of tax non-compliance behaviour in the informal sector. The study highlights the factors that influence individuals to engage in tax non-compliance behaviour. To academic researchers, the study provides insightful recommendations on carrying out similar future studies with different methodology and populations to contribute to tax and compliance research.
MPhil. Accounting
Keywords: Corruption Perception; Tax Non-Compliance; Self-Employed; Ghana